PEDAGOGICAL APPROACHES TO THE ORGANIZATION OF INDEPENDENT WORK OF STUDENTS OF THE PHILOLOGICAL DIRECTION - Akhmedova, Malokhat (MMIT Proceedings, 2023)
Didactic approach on the basis of integrated education from the subjects of pedagogical and native language teaching literacy methodology of students in education on the basis of the current state and prospects in the development of independent conducting assignments, the principles of didactic approach to higher education institutions on the basis of advanced world experiences, recognition of educational, educational results. The educational trajectory is based on the fact that it is advisable to introduce a didactic system from the subjects of pedagogy and the teaching of the native language literacy methodology